Variant Cells and Viral Infections: Understanding Cellular Coping Mechanisms - Farzaneh Sheikholeslami1*; Reza Shirzad1; Fatemeh Motevalli2 (Journal of Medical Microbiology and Infectious Diseases)
Cellular stress, induced by diverse factors including viral infection, reactive oxygen species (ROS), hypoxia, and toxin exposure, disrupts normal cellular function. The endoplasmic reticulum (ER) is pivotal in managing cellular stress, notably through the unfolded protein response (UPR) and ERassociated degradation (ERAD) pathways. This intricate process involves a complex interplay of transcription factors and signaling molecules. During viral infection, cells activate a multifaceted antiviral response, which is specifically modulated by both the virus type and the molecular mechanisms of the host's immune system. For instance, certain viruses like Japanese encephalitis virus (JEV) exploit multiple cellular pathways for replication and propagation. Viral infection can significantly impact cellular processes like autophagy and apoptosis, either promoting or suppressing these pathways. Thus, the cellular response to viral infection represents a dynamic interplay that can either benefit the host or be exploited by the virus for its propagation. For instance, viruses within the Flaviviridae family often preserve host cell viability during early infection to enhance replication, subsequently triggering apoptosis or other cell death mechanisms to facilitate viral dissemination. This review explores the diverse responses of infected cells to various viruses, highlighting the complex molecular strategies employed by both host and pathogen.